Perioperative events influence cancer recurrence risk after surgery - Hiller, Jonathan G; Perry, Nicholas J; Poulogiannis, George; Riedel, Bernhard; Sloan, Erica K (Nature reviews. Clinical oncology, 2018)
Surgery is a mainstay treatment for patients with solid tumours. However, despite surgical resection with a curative intent and numerous advances in the effectiveness of (neo)adjuvant therapies, metastatic disease remains common and carries a high risk of mortality. The biological perturbations that accompany the surgical stress response and the pharmacological effects of anaesthetic drugs, paradoxically, might also promote disease recurrence or the progression of metastatic disease. When cancer cells persist after surgery, either locally or at undiagnosed distant sites, neuroendocrine, immune, and metabolic pathways activated in response to surgery and/or anaesthesia might promote their survival and proliferation. A consequence of this effect is that minimal residual disease might then escape equilibrium and progress to metastatic disease. Herein, we discuss the most promising proposals for the refinement of perioperative care that might address these challenges. We outline the rationale and early evidence for the adaptation of anaesthetic techniques and the strategic use of anti-adrenergic, anti-inflammatory, and/or antithrombotic therapies. Many of these strategies are currently under evaluation in large-cohort trials and hold promise as affordable, readily available interventions that will improve the postoperative recurrence-free survival of patients with cancer.